Pelatihan Penerapan Muatan Pembelajaran IPAS Sesuai dengan Kurikulum Merdeka di SD Negeri Maleber - Acesta, Arrofa; Wulandari, Isnaini; Oktaviani, Ndaru Mukti (Society : Jurnal Pengabdian Masyarakat, 2024)
Quality education is a right for every citizen. One of the efforts made by the government to improve the quality of education is through curriculum development. The Merdeka Curriculum is the latest curriculum implemented in Indonesia. Based on interviews with the Principal of SD Negeri Maleber, it was found that most teachers have already received socialization regarding the implementation of the Merdeka Curriculum. Teachers have also started to learn independently about the process of its implementation. However, teachers are still experiencing difficulties in implementing the IPAS (Integrated Science) subject content as stipulated in the Merdeka Curriculum. This condition certainly needs to be addressed in order to improve teacher professionalism.Based on the problems faced by teachers at SD Negeri Maleber, teachers need knowledge and improved skills in implementing IPAS subject content as stipulated in the Merdeka Curriculum. This forms the basis for conducting the "Training on Implementing IPAS Subject Content According to the Merdeka Curriculum at SD Negeri Maleber."The objectives of this service are:To provide teachers with knowledge about the IPAS subject content in the Merdeka Curriculum.To provide skills training for teachers on how to implement the IPAS subject content in the Merdeka Curriculum.